Consciência e estados modificados de consciência em psicoterapias - Simões, Mário (1996)
Consciousness is defined and a relation is established between its altered states of consciousness (ASC) and as well to the ways how they are provoked. Phenomenology of ASC is described and related to psychopathology. A short commentary is made about ASC used in some ethnopsychotherapy. Psychotherapy, of western origin, using ASC, specially hypnosis, directed day-dream (rêve éleillé dirigé) of Desoille, katathymic experienced imagery (katathymes Bilderleben) of Leuner and regressive personalized and experienced imaginary (regression and past-lives therapy) are presented and commented.